Investasi Aceh: Wujud Kontribusi Etika Pada Pengusaha dan Pemerintah - lia safrina (I-Finance Journal, 2022)
This study aims to identify the development of investment, the contribution of government and entrepreneurs in investment development and the application of Islamic investment in Aceh. This research is qualitative and analyzed using descriptive analysis. Data collection methods were conducted by means of unstructured observation and in-depth interviews with informants. This research provides results that; 1). Investment realization in Aceh has increased by 56.76% from 2019-2020, this achievement exceeds the target set in the Aceh RPJM document with an investment realization value of 150.60%, 2). The government and entrepreneurs have contributed well to the development of investment in Aceh. 3) The implementation of investment in Aceh has fulfilled the aspects of investment in Islam both from the material or financial aspects, halal aspects, social and environmental aspects and aspects of hope in the pleasure of Allah SWT. The conclusion of Aceh's investment development in 2020 experienced a fairly positive improvement compared to previous years, the application of investment in Aceh has fulfilled the aspects of investment in Islam, this condition can foster the attractiveness of investors both from local and outside Aceh to invest in Aceh.